Polydimethylsiloxane-assisted plasma electrolytic oxidation of Ti for synthesizing SiO2-TiO2 composites for application as Li-ion battery anodes - Han-Gyoul Gim; Yong-Tae Kim; Jinsub Choi (Electrochemistry Communications, 2023)
A SiO2-TiO2 composite electrode with the synergistic effects of a stable cycle performance of TiO2 and high theoretical capacity of SiO2 was prepared through the plasma electrolytic oxidation (PEO) of Ti. When a polydimethylsiloxane (PDMS) layer is spin-coated on a Ti substrate (PDMS@Ti), the PEO reaction effectuates immediately on the pristine Ti, where the bubble phase forms first and PEO occurs for an extended period of time at a low voltage. Significantly, compared to the composite film prepared on pristine Ti, the SiO2-TiO2 composite film with a thickness of 80.39 μm exhibits large pores, which are beneficial for facilitating the transportation of Li+ with large amounts of Si. Consequently, a higher areal capacity of 1505.35 μAh cm−2 at a current density of 500 μA cm−2 was achieved compared to that of pristine Ti.